2021
DOI: 10.1186/s12885-021-07965-8
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of a decision support algorithm to improve clinicians’ chemotherapy-induced peripheral neuropathy assessment and management practices: a two-phase, longitudinal study

Abstract: Background Chemotherapy-induced peripheral neuropathy (CIPN) negatively affects physical function and chemotherapy dosing, yet, clinicians infrequently document CIPN assessment and/or adhere to evidence-based CIPN management in practice. The primary aims of this two-phase, pre-posttest study were to explore the impact of a CIPN clinician decision support algorithm on clinicians’ frequency of CIPN assessment documentation and adherence to evidence-based management. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 41 publications
0
20
0
1
Order By: Relevance
“…Changing the practice of oncology clinicians can insufficiently be achieved by providing algorithms or guidelines, as shown by examples from chemotherapy-induced peripheral neuropathy 93 or chemotherapy-induced nausea and vomiting. 94 In contrast, training of specific skills can be effective in improving shared decisio-making.…”
Section: Discussionmentioning
confidence: 99%
“…Changing the practice of oncology clinicians can insufficiently be achieved by providing algorithms or guidelines, as shown by examples from chemotherapy-induced peripheral neuropathy 93 or chemotherapy-induced nausea and vomiting. 94 In contrast, training of specific skills can be effective in improving shared decisio-making.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the list of excluded studies at full-text screening stage can be found in the Supplement (eTable 1). A total of six studies published between 2017 and 2021, two stepped-wedge cluster RCTs [30,31] and four controlled NRSIs with before-and after study design [32][33][34][35], were included in the synthesis. Further, ve ongoing trials were identi ed [36][37][38][39][40] and four studies were categorised as awaiting classi cation (due to no published results and a conference abstract with insu cient information), of which all were randomized [41][42][43][44].…”
Section: Resultsmentioning
confidence: 99%
“…The six included studies assessed multi-component guideline implementation interventions compared to no intervention in 2024 cancer patients and 281 healthcare professionals [30][31][32][33][34][35]. The most frequently used strategies, which were applied in all six interventions, were educational meetings and educational materials (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…In summary, participants were a median of 57 (Range: 27-80) years old, and predominantly female (66%), Caucasian (90%), received undergraduate (33.1%) or post graduate degree training (32.4%), working fulltime (38%), diagnosed with a gastrointestinal (51%) or breast (37%) malignancy or multiple myeloma (11%), and receiving platinum (50%) (e.g., common treatment for gastrointestinal malignancies), taxane (35.9%) (e.g., common treatment for breast cancer), or proteasome-inhibitor-based (11%) cancer therapy (e.g., common treatment for multiple myeloma). Approximately 56% of the sample had received ≥ two-thirds of their planned course of neurotoxic therapy by T3 [22].…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…Specifically, we estimated the floor and ceiling effects, test-retest reliability, concurrent validity, longitudinal validity, construct validity of the response categories, and sensitivity and specificity of the PRO-CTCAE numbness and tingling severity and interference items in cancer patients receiving taxanes, platinums, or proteasome inhibitors. impact of a clinician decision support algorithm on clinicians' documentation of CIPN assessment and management [22]. The sample consisted of 142 English speaking patients with breast or gastrointestinal cancer, or multiple myeloma who had received ≥ one infusion of neurotoxic therapy (e.g., taxanes, platinums, or proteasome inhibitors) at the time of consent and were scheduled to receive ≥ three more cycles of neurotoxic therapy.…”
Section: Introductionmentioning
confidence: 99%